2013
DOI: 10.1371/journal.pone.0063627
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Is a Key Regulator of Myoblast Differentiation

Abstract: Transthyretin (TTR) is a known carrier protein for thyroxine (T4) and retinol-binding protein in the blood that is primarily synthesized in the liver and choroid plexus of the brain. Herein, we report that the TTR gene is expressed in skeletal muscle tissue and up-regulated during myotube formation in C2C12 cells. TTR silencing (TTRkd) significantly reduced myogenin expression and myotube formation, whereas myogenin silencing (MYOGkd) did not have any effect on TTR gene expression. Both TTRkd and MYOGkd led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Although the importance of TH signaling in muscle physiology has been documented for several years, its precise mechanism in skeletal muscle during postnatal myogenesis remains unclear. Initially, we demonstrated the role of TTR in sustaining the cellular T 4 level during myoblast proliferation and differentiation [6,29]. In this study, we give the first direct evidence of TTR secretion and uptake in C2C12 mouse myoblast cells.…”
Section: Discussionmentioning
confidence: 59%
“…Although the importance of TH signaling in muscle physiology has been documented for several years, its precise mechanism in skeletal muscle during postnatal myogenesis remains unclear. Initially, we demonstrated the role of TTR in sustaining the cellular T 4 level during myoblast proliferation and differentiation [6,29]. In this study, we give the first direct evidence of TTR secretion and uptake in C2C12 mouse myoblast cells.…”
Section: Discussionmentioning
confidence: 59%
“…The mechanisms underlying processes that regulate skeletal muscle specification and formation are of considerable research interest in the context of muscle plasticity (37, 38). Initially, we used high‐throughput techniques such as microarray, expressed sequence tag, and RNA‐seq analysis to identify the genes involved and investigated the multipotential capacity of MSCs to differentiate and transdifferentiate into myogenic and adipogenic cells (3941). During our study, several genes were found to be variously expressed during differentiation and transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion index was calculated as previously described by Lee et al [16]. Briefly, C2C12 cells grown to 70% confluence were switched to differentiation media and incubated for 5 days.…”
Section: Determination Of Fusion Index For Myotube Formationmentioning
confidence: 99%